Gender in constitutional law - MacKinnon, Catharine A., 1946-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
This accessible and incisive research review discusses a collection of formative and influential scholarship in a particularly dynamic area of legal development and social change: the role of gender within constitutional law. It features theoretical, empirical, and practical analyses from leading scholars, judges, and nongovernmental organizations around the world. The review is transnational and comparative in range and representative in scope, with particular attention paid to intersectionality, culture and custom. Written by an internationally renowned scholar, lawyer and activist, this review is an essential research tool for libraries, academic institutions, scholars and students alike.
14. Kimberlé Crenshaw (1991), 'Mapping the Margins: Intersectionality, Identity Politics, and Violence Against Women of Color', Stanford Law Review, 43 (6), July, 1241-99 -- 15. Kate O'Regan (2013), 'The Right to Equality in the South African Constitution', Columbia Journal of Gender and Law: Symposium Honoring Justice Ruth Bader Ginsburg, 25 (1), 110-15 -- 16. Valorie K. Vojdik (2008), 'Conceptualizing Intimate Violence and Gender Equality: A Comparative Approach', Fordham International Law Journal, 31 (2), 487-527 -- 17. John Borrows (2013), 'Aboriginal and Treaty Rights and Violence Against Women', Osgoode Hall Law Journal, 50 (3), Spring, 699-736 -- 18. Catharine A. MacKinnon (2004), 'The Road Not Taken: Sex Equality in Lawrence v. Texas', Ohio State Law Journal, 65 (5), 1081-95 -- 19. William N. Eskridge, Jr. (2010), 'Sexual and Gender Variation in American Public Law: From Malignant to Benign to Productive', UCLA Law Review, 57 (5), June, 1333-73 ---20. Bret Boyce (2015), 'Sexuality and Gender Identity Under the Constitution of India', Journal of Gender, Race and Justice, 18 (1), Winter, 1-64 -- 1. Christine Chinkin (2001), 'Gender Mainstreaming in Legal and Constitutional Affairs: A Reference Manual for Governments and Other Stakeholders', Commonwealth Secretariat, 1-102 -- 2. Georgina Waylen (2006), 'Constitutional Engineering: What Opportunities for the Enhancement of Gender Rights?', Third World Quarterly: The Politics of Rights: Dilemmas for Feminist Praxis, 27 (7), 1209-21 -- 3. Angela M. Banks (2007), 'Challenging Political Boundaries in Post-Conflict States', University of Pennsylvania Journal of International Law, 29 (1), 105-68 -- 4. Cathi Albertyn and Beth Goldblatt (2008), 'Towards a Substantive Right to Equality', in Stu Woolman and Michael Bishop (eds.) Constitutional Conversations, Chapter 14, Pretoria, South Africa: Pretoria University Law Press, 231-254 ---5. Aili Mari Tripp (2009), 'Conflicting Agendas? Women's Rights and Customary Law in African Constitutional Reform', in Susan H. Williams (ed.) Constituting Equality: Gender Equality and Comparative Constitutional Law, Chapter 8, New York, NY, USA: Cambridge University Press, 173-94 -- 6. Susan Bazilli and Marilou McPhedran (2009), 'Women's Constitutional Activism in Canada and South Africa', International Review of Constitutionalism, 9 (2), 389-418 -- 7. Claudia Flores and Patricia A. Made (2013), 'The Politics of Engagement: Women's Participation and Influence in Constitution-making Processes', UN Women: United Nations Entity for Gender Equality and the Empowerment of Women Report, i, iii-v, vii, 1-48 -- 8. Kathleen S. Fine-Dare (2014), 'The Claims of Gender: Indigeneity, Sumak Kawsay, and Horizontal Women's Power in Urban Ecuador under the 2008 Political Constitution', Social Development Issues: Alternative Approaches to Global Human Needs, 36 (3), November, 18-33 ---9. Pilar Domingo, Aoife McCullough, Florence Simbiri and Bernadette Wanjala (2016), 'Women and Power: Shaping the Development of Kenya's 2010 Constitution', Overseas Development Institute Report, March, 1, 3-44 -- 10. Mounira Maya Charrad (2016), 'Progressive Law: How it Came About in Tunisia', Journal of Gender, Race and Justice, 18 (2), Spring, 351-9 -- 11. Hallie Ludsin (2011), 'Women and the Draft Constitution of Palestine', Women's Centre for Legal Aid and Counselling Report, 1, 3-262
The recommended readings are available in the print version, or may be available via the link to your library's holdings
Keywords: ústavní právo; gender; constitutional law; gender; e-knihy online; e-books online